2022
DOI: 10.2147/prbm.s343135
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Moral Disengagement and Learned Helplessness Towards International Postgraduate Students’ Academic Procrastination

Abstract: Objective Supervisors play an important role in international postgraduate students’ academic performance, their insufficient guidance and supervision are the main antecedents for international postgraduate students’ academic procrastination. Meanwhile, international postgraduate students’ disengagement tendency and learned helplessness in dealing with supervisor’s moral disengagement will significantly affect their academic choices and outcomes. Methods Based on self-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
1
4
0
5
Order By: Relevance
“…Also, according to the research findings, academic hope is directly related to academic enthusiasm. This finding is with the results by Chena et al (2020) , Farid and Ashrafzade (2021) , Snyder et al (2002) , and Wu and He (2022) are consistent. Sohrabi et al (2021) concluded in their research that there is a positive and significant relationship between students’ hope and academic enthusiasm, and hopeful students have more academic enthusiasm.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Also, according to the research findings, academic hope is directly related to academic enthusiasm. This finding is with the results by Chena et al (2020) , Farid and Ashrafzade (2021) , Snyder et al (2002) , and Wu and He (2022) are consistent. Sohrabi et al (2021) concluded in their research that there is a positive and significant relationship between students’ hope and academic enthusiasm, and hopeful students have more academic enthusiasm.…”
Section: Discussionsupporting
confidence: 92%
“…The results of Laslo-Roth et al (2022) also showed that people with higher academic enthusiasm have higher academic motivation, are more hopeful about their academic future, and feel higher self-regulation. A study of more than 20 years of research in the field of hope shows that more hopeful students in education and life, show better performance than other students and have higher academic enthusiasm ( Wu and He, 2022 ).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…У недавніх дослідженнях аспекти п'ятифакторної моделі були застосовані до академічної прокрастинації [11]. Основними причинами прояву академічної прокрастинації є порушення у технічній стороні діяльності та невміння суб'єктів навчання розставляти пріоритети у своїй роботі, іншими словами, у них спостерігається несформованість навичок тайм-менеджменту, що призводить до непослідовності, безсистемності дій та нездатності довгий час зосереджуватися на проблемі [1].…”
Section: аналіз літературиunclassified
“…Вивчена безпорадність проявляється як стан когнітивного дисбалансу та втоми. Люди схильні внутрішньо приписувати невдачу події, що призводить до їхньої когнітивної дилеми відсутності впевненості і підриває їхню здатність виконувати завдання, щоб максимально уникнути прийняття цільового рішення і відмовитися від пошуку шляхів подолання труднощів [11].…”
Section: результати дослідженняunclassified